Neutrophils disturb pulmonary microcirculation in sepsis-induced acute lung injury. Issue 3 (28th March 2019) - Park, Inwon; Kim, Mingyo; Choe, Kibaek; Song, Eunjoo; Seo, Howon; Hwang, Yoonha; Ahn, Jinhyo; Lee, Seung-Hyo; Lee, Jae Hyuk; Jo, You Hwan; Kim, Kyuseok; Koh, Gou Young; et al.
The lung is highly vulnerable during sepsis, yet its functional deterioration accompanied by disturbances in the pulmonary microcirculation is poorly understood. This study aimed to investigate how the pulmonary microcirculation is distorted in sepsis-induced acute lung injury (ALI) and reveal the underlying cellular pathophysiologic mechanism. Using a custom-made intravital lung microscopic imaging system in a murine model of sepsis-induced ALI, we achieved direct real-time visualisation of the pulmonary microcirculation and circulating cells in vivo . We derived the functional capillary ratio (FCR) as a quantitative parameter for assessing the fraction of functional microvasculature in the pulmonary microcirculation and dead space. We identified that the FCR rapidly decreases in the early stage of sepsis-induced ALI. The intravital imaging revealed that this decrease resulted from the generation of dead space, which was induced by prolonged neutrophil entrapment within the capillaries. We further showed that the neutrophils had an extended sequestration time and an arrest-like dynamic behaviour, both of which triggered neutrophil aggregates inside the capillaries and arterioles. Finally, we found that Mac-1 (CD11b/CD18) was upregulated in the sequestered neutrophils and that a Mac-1 inhibitor restored the FCR and improved hypoxaemia. Using the intravital lung imaging system, we observed that Mac-1-upregulated neutrophil aggregates led to the generation of dead space in the pulmonary microcirculation that was recovered by a Mac-1 inhibitor in sepsis-induced ALI. Neutrophils induce dead space in the pulmonary microcirculation in sepsis-induced ALI, recovered by a Mac-1 inhibitor http://ow.ly/vUzO30nbUyU